Associations Between Late Pregnancy Dietary Inflammatory Index (DII) and Offspring Bone Mass: A Meta‐Analysis of the Southampton Women's Survey (SWS) and the Avon Longitudinal Study of Parents and Children (ALSPAC). (4th July 2022) - Woolford, Stephen J; D'Angelo, Stefania; Mancano, Giulia; Curtis, Elizabeth M; Ashai, Shanze; Shivappa, Nitin; Hébert, James R; Crozier, Sarah R; Phillips, Catherine M; Suderman, Matthew; Relton, Caroline L; Cooper, Cyrus; et al.
ABSTRACT: Systemic inflammation is associated with reduced bone mineral density and may be influenced by pro‐inflammatory diets. We undertook an observational analysis of associations between late pregnancy energy‐adjusted dietary inflammatory index (E‐DII) scores and offspring bone outcomes in childhood. E‐DII scores (higher scores indicating pro‐inflammatory diets) were derived from food frequency questionnaires in late pregnancy in two prospective mother‐offspring cohorts: the Southampton Women's Survey (SWS) and the Avon Longitudinal Study of Parents and Children (ALSPAC). The mean (SD) offspring age at dual‐energy X‐ray absorptiometry (DXA) scanning was 9.2 (0.2) years. Linear regression was used to assess associations between E‐DII and bone outcomes, adjusting for offspring sex and age at DXA and maternal age at childbirth, educational level, pre‐pregnancy body mass index (BMI), parity, physical activity level, and smoking in pregnancy. Associations were synthesized using fixed‐effect meta‐analysis. Beta coefficients represent the association per unit E‐DII increment. In fully adjusted models (total n = 5910) late pregnancy E‐DII was negatively associated with offspring whole body minus head bone area (BA: β = −3.68 [95% confidence interval −6.09, −1.27] cm 2 /unit), bone mineral content (BMC: β = −4.16 [95% CI −6.70, −1.62] g/unit), and areal bone mineral density (aBMD: β = −0.0012 [95% CI −0.0020, −0.0004] g.cm −2 /unit), but there was only a weak association with BMC adjusted for BA (β = −0.48 [95% CI −1.11, 0.15] g/unit) at 9 years. Adjustment for child height partly or, for weight, fully attenuated the associations. Higher late pregnancy E‐DII scores (representing a more pro‐inflammatory diet) are negatively associated with offspring bone measures, supporting the importance of maternal and childhood diet on longitudinal offspring bone health. © 2022 The Authors. Journal of Bone and Mineral Research published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research (ASBMR).